PHYTO CHEMICAL COMPOSITION AND In vitro ANTIPLASMODIAL POTENTIAL OF STEM BARK AND LEAF EXTRACTS OF Ficus gnaphalocarpa AND Ipomea fistulos USED IN YAURI AND ARGUNGU EMIRATES, KEBBI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Malaria is the world’s most parasitic disease endemic in about 100 developing countries. The search for new antimalarial drugs from natural products is necessitated by resistance of the parasites to known antimalarial agents. This study  evaluated  phytocmical composition and the in vitro antiplasmodial potentials of Ficus gnaphalocarpa stem bark and Ipomea fistulos leaf methanolic extracts  obtained from two  areas (one each from Argungu and Yauri emirates of Kebbi State, Nigeria ) . The air dried samples of Ficus gnaphalocarpa (miq) C.C. Beng (stem bark) and Ipomea fistulos L. (leaves) were extracted with methanol for seventy two hours. The crude extracts were tested against chloroquine resistant strain of Plasmodium berghei berghei (NK-65) in vitro in 96 well microplates under anaerobic condition. The data obtained were analyzed using one way ANOVA and Duncan multiple comparison test with SPSS version 20.0. There was significant (P
Keywords: Antiplasmodial activity, Plasmodium berghei berghei, Ficus gnaphalocarpa, Ipomea fistulos, malaria